(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article is about how the last stages of pregnancy occur, the onset of labor and the main signs of it, and the knowledge that a nurse should have in this situation. The readiness of a pregnant woman for childbirth is determined mainly by the nature of the contractions of the uterus and the characteristics of the cervix. The nature of the contractions of the uterine muscles can be determined manually and with the help of special devices.